Evaluasi Infrastruktur Terhadap Pertumbuhan Ekonomi Provinsi Gorontalo Tahun 2010-2024 - Anisah Masri Ibrahim; Muhammad Amir Arham; Sri Indriyani S. Dai (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of road infrastructure, electricity infrastructure, and drinking water infrastructure on the economic growth of Gorontalo Province. The type of data used in this research is secondary time series data obtained from the Central Statistics Agency (BPS) of Gorontalo Province and other related literature. The data consist of annual observations from 2010 to 2024.The analytical methods used include descriptive analysis and quantitative analysis with a multiple regression model. The results show that road infrastructure has a positive but insignificant effect on the economic growth of Gorontalo Province. This means that road development can encourage economic growth, but its impact is not yet clearly visible or remains relatively weak. Electricity infrastructure has a negative but insignificant effect on economic growth, indicating that the availability of electricity has not yet provided a real impact on economic growth and appears less supportive, although its influence is not clearly reflected in increasing or decreasing the growth rate. Drinking water infrastructure has a negative and significant effect on economic growth in Gorontalo Province. This means that the greater the expenditure on drinking water infrastructure, the lower the economic growth, and this effect is statistically proven and not coincidental.